The Pilgrims’ Method in Proving Baath in Noble Systems between Al-Makki and Al-Mady is an Analytical Synagogue - Al-Shahri, Mohsen Ali Mohammad (Journal of Islamic Sciences, 2019)
This research is entitled "Pilgrims’ Method in Proving Baath between Mekki and Medani" This study shows the way pilgrims practice in the noble systems, especially since this method is represented in most important issues that the regimes wanted to decide in souls, including the case of proving Baath, and the denial of the other day was of bad humiliation, so the pilgrims came to prove the other day in accordance with the intentions of Al-Maki and Al-Madni, and in accordance with the context of each Sura. The study was carried out within the framework of the analytical descriptive method, and the research dealt with a brief introduction of research, the researcher’s approach, and the research problem, and the research was divided into six discussions: The first research explained the concept of pilgrims, and presented its rhetorical value, and the second study showed the difference between the Holy Quran and the third research that started on two verses of the Holy Qur’an in his argument to prove the Baath, and then showed how the fourth was discussed